Passive samplers of hydrophobic organic chemicals reach equilibrium faster in the laboratory than in the field. Issue 1 (15th September 2015) - Booij, Kees; Tucca, Felipe
Graphical abstract: Highlights: Passive sampler equilibration times in closed and open systems are very different. Depletion of the water accelerates equilibration in finite water volumes. The concept "sorption capacity" gives a better understanding of equilibration times. Abstract: The use of passive sampling methods for monitoring hydrophobic organic chemicals frequently requires the determination of equilibration times and partition coefficients in the laboratory. These experiments are often carried out by exposing passive samplers in a finite water volume, and errors are easily made when the obtained results are applied to the field, where water volumes are essentially infinite. The effect of water volume on the equilibration rate constant is discussed, using a mechanistic model. Application of this model to two literature reports illustrates that aqueous concentrations in the field may be underestimated by a factor of 10 or more, when the water volume effect is neglected. Finally, it is shown that the concept of "sorption capacity" (sampler mass times partition coefficient) allows for a more intuitive understanding of the passive sampling process in small and large water volumes, which may reduce the risk of laboratory-field extrapolation errors.